Manajemen Sekolah Berbasis Kopi Pada Sekolah Menengah Pertama Islam Terpadu Al-Fatih Boarding School Bener Meriah - Musradinur, Musradinur; Andriansyah, Andriansyah; Putri, Diana (Intelektualita: Journal of Education Sciences and Teacher Training, 2024)
School-Based Management is one solution to solving problems in the education system in Indonesia. With School-Based Management, educational institutions will be more independent in determining the direction of their school development, and can carry out more independent innovations. One of the potentials and natural riches possessed by Bener Meriah district is coffee, which is known as one of the best coffee producing regions in the world with high quality coffee products but the younger generation lacks knowledge about coffee as a superior commodity, the establishment of a coffee-based school in Bener Meriah district has become a new color among young people to be able to learn more deeply about superior commodities in the Gayo Highlands. The coffee-based school in Bener Meriah Regency is SMP IT Al-Fatih Boarding School. Coffee-based school management at Al-Fatih Boarding School Integrated Islamic Junior High School has been effective. The Contribution of Coffee to School-Based Management at the Integrated Islamic Junior High School Al-Fatih Boarding School is that coffee is a source of financing for schools to support independent education. In coffee-based school management, there are challenges in managing coffee-based school management at the Al-Fatih Integrated Islamic Junior High School, including the lack of teachers in the coffee sector and inadequate infrastructure.